Every breath counts: Lessons learned in developing a training NICU in Northern Tanzania - Swanson, Stephen J.; Martinez, Kendra K.; Shaikh, Henna A.; Philipo, Godbless M.; Martinez, Jarian; Mushi, Evelyine J. (Frontiers in Pediatrics, 2022)
Neonatal mortality rates in resource-limited hospitals of Sub-Saharan Africa (SSA) remain disproportionately high and are likely underestimated due to misclassification of extremely preterm births as “stillbirths” or “abortions”, incomplete death registries, fear of repercussions from hospital and governmental authorities, unrecorded village deaths, and cultural beliefs surrounding the viability of premature newborns. While neonatology partnerships exist between high income countries and hospitals in SSA, efforts have largely been directed towards improving newborn survival through neonatal resuscitation training and provision of equipment to nascent neonatal intensive care units (NICUs). These measures are incomplete and fail to address the challenges which NICUs routinely face in low-resource settings. We draw on lessons learned in the development of a low-technology referral NICU in Tanzania that achieved an overall 92% survival rate among infants. Achieving high survival rates among critically ill and preterm neonates in SSA is possible without use of expensive, advanced-skill technologies like mechanical ventilators. Evidence-based protocols adapted to low-resource hospitals, mentorship of nurses and physicians, changes in hierarchal culture, improved nurse-infant staffing ratios, involvement of mothers, improved procurement of consumables and medications, and bedside diagnostics are necessary steps to achieving high survival rates. Our NICU experience indicates that low-technology solutions of thermoregulation, respiratory support via continuous positive airway pressure, feeding protocols and infection control measures can ensure that infants not only survive, but thrive. Neonatal mortality and survival of preterm newborns can be improved through a long-term commitment to training NICU staff, strengthening basic neonatal care practices, contextually appropriate protocols, and limited technology.